ACTIVATION OF GENETIC PROCESSES IN PROKARYOTES IN THE PRESENCE OF DOUBLE-STRAND RNA (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
The study of the influence of double-strand RNA (ds-RNA) on genetic transformation and conjugation processes has been carried out in a wide range of gramnegative bacteria species. It has been shown that ds-RNA in the presence of CaCl2 in 10 µg/mL and 1 mM concentrations respectively efficiently increases the frequency of genetic exchange. The above mentioned concentrations of only ds-RNA or CaCl2 separately don’t cause the same effect.
Keywords: double-strand RNA; genetic transformation; conjugation processes; gramnegative bacteria